Prophetic Leadership and Teacher Competence: A Quantitative Study in Indonesian Secondary Islamic and Public Schools - Muslihah, Eneng; Ma'mur, Ilzamudin; Mubarok, Asep Syahrul (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
Education in this country until now is still overshadowed by various problems. These multiple problems have serious consequences for the quality of education. In this case, the leadership aspect is part of the pillars supporting education. Prophetic leadership is the ideal form of leadership, which, of course, influences the quality of education, especially teacher competence. The author is interested in conducting a correlational study of prophetic leadership and teacher competence to examine how prophetic leadership relates to and contributes to teacher competence. The method used in this research is the quantitative correlation method. This research shows that prophetic leadership significantly influences teacher competence. Based on the results of the correlation test, both at MTsN 1 Serang City and at SMPN 1 Baros Serang Regency, the prophetic leadership of educational institution heads significantly contributes to PAI teachers' competency. Still, the degree of correlation differs between the two. The prophetic leadership of the head of the institution at SMPN 1 Baros, Serang Regency, shows a strong correlation. In contrast, at MTsN 1 Serang City, the correlation is moderate. Future research should include a larger, more diverse sample, examine longitudinal data, and consider additional qualitative dimensions to capture better how prophetic leadership influences teacher competence development across various educational settings. This study is limited to two academic institutions in Serang, making broad generalizations difficult. It also does not account for potential moderating factors such as institutional culture, teacher demographics, or leadership training experiences.